Implementasi Metode Enkripsi Pergeseran Biner Dengan Microsoft Visual Basic 6.0 - Prakoso, Kusuma; ., Haryani; Nugroho, Gesang Kristianto (Speed - Sentra Penelitian Engineering dan Edukasi, 2009)
System bind on computer personal using platform of Microsoft Windowsâ¢ as machine of activator of public system because cannot prevent all hacker, cracker and attacker to enter and exploit the content from pertinent computer system for the sake of negativity. Especially at network of computer of peer to peer own the Microsoft Windowsâ¢ and public network [of] internet. So that as for how to conduct the implementation of binary method encryption shifting with Visually Basic 6.0 competent to be strived. This research aim to to prove that competent binary method encryption shiftingÂ  implemented in everyday life all civil consumer for the protection of their data from acting cyber-crime, providing application program light cryptography and easy to just used by whom and for the sake of any kind of, security importance applicable to bind the static (in a stand alone computer and local of area network) and also in a community owning to bind the dinamic (mobile) such as a community in (virtual) private network and public network (internet) and also in physical delivery. The result of this research can present the data qualitative result of technical measurement and examination according to principles of software engineering so that application elegibility result of accountable engineering.